Cardiac Risk Stratification in Liver Transplantation: Results of a Tiered Assessment Protocol Based on Traditional Cardiovascular Risk Factors. Issue 7 (9th July 2021) - Robertson, Marcus; Chung, William; Liu, Dorothy; Seagar, Rosemary; O'Halloran, Tess; Koshy, Anoop N.; Horrigan, Mark; Farouque, Omar; Gow, Paul; Angus, Peter
Abstract : Coronary artery disease (CAD) confers increased perioperative risk in patients undergoing liver transplantation (LT). Although routine screening for CAD is recommended, there are limited data on the effectiveness of screening strategies. We evaluated the safety and efficacy of a 3‐tiered cardiac risk‐assessment protocol that stratifies patients based on age and traditional cardiac risk factors. We peformed a single‐center, prospective, observational study of consecutive adult patients undergoing LT assessment (2010‐2017). Patients were stratified into low‐risk (LR), intermediate‐risk (IR), or high‐risk (HR) cardiac groups and received standardized investigations with selective use of transthoracic echocardiography (TTE), dobutamine stress echocardiography (DSE), computed tomography coronary angiography (CTCA), and coronary angiography (CA). Primary outcomes were cardiac events (CEs) and cardiovascular death up to 30 days after LT. Overall, 569 patients were included, with 76 patients identified as LR, 256 as IR, and 237 as HR. Cardiac risk factors included diabetes mellitus (26.0%), smoking history (47.3%), hypertension (17.8%), hypercholesterolemia (7.2%), family (17.0%) or prior history of heart disease (6.0%), and obesity (27.6%). Of the patients, 42.0% had ≥2 risk factors. Overall compliance with the protocol was 90.3%. Abnormal findings on TTE, DSE, and CTCA were documented in 3, 23, and 44 patients, respectively, and 12 patients were not listed for transplantation following cardiac assessment (1 LR, 2 IR, and 9 HR). Moderate or severe CAD was identified in 25.4% of HR patients on CTCA following a normal DSE. CEs were recorded in 7 patients (1.2%), with 2 cardiovascular deaths (0.4%). Cardiac risk stratification based on traditional cardiac risk factors with the selective use of DSE, CTCA, and CA is a safe and feasible approach that results in a low perioperative cardiac event rate.